Structural elucidation of an asparagine-linked oligosaccharide from the hyperthermophilic archaeon, Archaeoglobus fulgidus. (2nd September 2015) - Fujinami, Daisuke; Nyirenda, James; Matsumoto, Shunsuke; Kohda, Daisuke
Abstract: The genome of the hyperthermophilic archaeon, Archaeoglobus fulgidus, contains three paralogous AglB genes that encode oligosaccharyltransferase (OST) proteins. The OST enzymes catalyze the transfer of an oligosaccharide chain from lipid-linked oligosaccharides (LLO) to asparagine residues in proteins. The detergent-solubilized membrane fractions prepared from cultured A. fulgidus cells contain both OST and LLO. The addition of a peptide containing the glycosylation sequon produced oligosaccharide chains attached to a structurally defined peptide. To facilitate the NMR analysis, the cells were grown in rich medium supplemented with 13 C -glucose, to label the LLOs metabolically. The MS analysis of the glycopeptide revealed that the glucose and galactose residues were nearly fully 13 C-labeled, but the mannose residues were fractionally labeled with about 20% efficiency. An immunodetection experiment revealed that the longest AglB paralog ( Af AglB-L) was expressed in the membrane fractions under our cell culture conditions, while the other two shorter AglB paralogs ( Af AglB-S1 and Af AglB-S2) were not. Thus, the oligosaccharide chain analyzed in this study was the product of Af AglB-L. The N-glycan consists of eight hexose residues, as follows: The α1, 3-linked glucose is an optional residue branching from the distal mannose residue. The MS analysis of the minor HPLC peak of the in vitro oligosaccharyl transfer products also revealed an optional sulfate modification on the glucose residue directly linked to the Asn residue. The present data will be useful for structural and functional studies of the N-glycosylation system of A. fulgidus . Graphical abstract: Highlights: Oligosaccharides attached to the Asn residue of a peptide were produced in vitro. 13 C labeled membrane fractions of Archaeoglobus fulgidus cells were used. The structure was established by chemical, NMR, and MS/MS analyses. The N-glycan is a novel oligosaccharide consisting of eight hexose residues.